Who is Disabled in Sub-Saharan Africa? - Montes, Jose; Swindle, Rachel (World Bank, Washington, DC, 2021)
Despite significant recent advances in research on people with disabilities in many developed countries, little is known about their counterparts living in the developing world. With the goal of helping to improve the state of knowledge on disability, the United Nations commissioned the Washington Group to develop a short set of questions to measure disability in official household surveys. This note uses the resulting data from ten recent surveys in Sub-Saharan Africa (SSA) to profile the characteristics of people with disabilities, briefly describing their welfare, gender, age, geographic characteristics, educational attainment, and labor force participation.